282PInhibition of miR-144 and miR-199 promote myeloma pathogenesis via upregulation of versican and FAK/STAT3 signaling. (24th November 2019) - Gupta, N; Kumar, R; Sharma, A
Abstract: Background: Multiple Myeloma (MM) is second most common hematological malignancy characterized by uncontrolled proliferation of abnormal plasma cells in bone marrow. microRNAs are newly emerged nowadays for their involvement in post-transcriptional regulation of certain genes. Earlier, we reported overexpression of an extracellular matrix protein, Versican (VCAN) in MM especially in the stroma but its involvement in disease pathogenesis has not been reported yet. Hence, we studied the role of VCAN via its regulation by microRNAs on myeloma pathogenesis. Methods: The molecular expression of VCAN was investigated in myeloma cell lines (RPMI8226 & U266). The antagomirs of microRNAs (miR-144 and miR-199) were then transfected into myeloma cells to investigate the effect on VCAN expression along with the effect on proliferation, apoptosis, migration and invasion of myeloma cells. In addition, signaling pathways affected by the inhibition of miR-144 and miR-199 were also identified. The functional regulation of VCAN by miR-144 and miR-199 was also confirmed by reporter luciferase assay in which VCAN 3'UTR was transfected to the myeloma cells. Results: The expression of VCAN was found at minimal level in both the myeloma cells. The transfection of antagomirs of miR-144 and miR-199 significantly enhanced the transcript and protein levels of VCAN in myeloma cells. Further, myeloma cells parameters found to be altered in favor of disease progression such as cell proliferation, migration and invasion increased with simultaneous inhibition of apoptosis. In addition, antagomirs mediated upregulation of VCAN promote myeloma progression via activation of FAK/STAT3 signaling. Moreover, transfection of wild type VCAN 3'UTR resulted in significant decrease in luciferase activity which got restored by mutating the binding site of microRNAs. Conclusions: miR-144 and mir-199 antagomirs mediated over-expression of VCAN promoted the myeloma pathogenesis in vitro with downstream activation of FAK and STAT3 signaling. These findings, therefore, affirm the translational importance of microRNAs which could be adopted as a mean for targeting VCAN and might emerge as an effective therapy for better management of MM in clinical settings in future. Legal entity responsible for the study: AIIMS, New Delhi, India. Funding: All India Institute of Medical Sciences, Council of Scientific and Industrial Research. Disclosure: All authors have declared no conflicts of interest.